Biochemical characterization of protein-digesting enzymes from viscera of bigfin reef squid (Sepioteuthis lessoniana) and implications for in vitro protein digestibility - Satjarak, Jirapan; Klomklao, Sappasith; Suanyuk, Naraid; Thongprajukaew, Karun (Agriculture and Natural Resources, 2023)
Importance of the work: Proteinase characteristics and digestibility screening can be used for nutritional investigations and the formulation of a suitable diet incorporating bigfin reef squid. Objective: To investigate the proteolytic activity and in vitro protein digestion of enzymes from the viscera of bigfin reef squid. Materials & Methods: The pH (2–11) and temperature (25–80°C) characteristics, stability, and inhibition of proteinases from viscera extracts of bigfin reef squid were investigated and the in vitro digestibility of five alternative protein ingredients were screened. Results: The highest activity of proteolytic enzymes was at pH 6 and 45°C. Three observed proteinases were stable in the pH range 5–11 and at temperatures of up to 40oC, for exposure times of 30–120 min. An inhibition study indicated that various proteinases were present in bigfin reef squid viscera. Based on in vitro digestibility, squid meat and brine shrimp were appropriate sources of alternative protein (p < 0.05). Digestibility values did not differ when squid meat was replaced with grade levels of soybean meal or fish meal (p > 0.05). Main findings: The optimal conditions for the major proteinases were pH 6 and 45°C. Based on their characteristics, the major proteinases were most likely chymotrypsin or chymotrypsin-like. The in vitro digestibility study suggested that squid meat could be replaced as a protein source with grade levels of soybean meal or fish meal.